Recontextualising Genre-Based Pedagogy in Indonesian Context: A Case of Preservice Teachers - Nurlaelawati, Iyen; Lengkanawati, Nenden Sri; Gunawan, Wawan (International Journal of Education, 2020)
This study focused on how two preservice teachers applied genre-based pedagogy in their teaching practices during teaching practicum in order to help their students produce descriptive report texts.  Using a case study design, the data were collected mainly from classroom observation and students’ texts. The findings showed that the preservice teachers had considerably good knowledge of genre-based pedagogy and of its application of the first two stages of the pedagogy. In the last two stages, they needed more attention to provide opportunities for the students to practice producing the focus text. In terms of the results of students’ learning, the preservice teachers needed improvement to support and observe the students’ development more closely in writing. This study suggests some evaluative results of how teaching practicum should support and help preservice teachers develop their professionalism in the field of EFL teaching.